2016
DOI: 10.1111/rda.12744
|View full text |Cite
|
Sign up to set email alerts
|

Identification of lactoferrin and glutamate receptor‐interacting protein 1 in bovine cervical mucus: A putative marker for oestrous detection

Abstract: Accurate detection of oestrus is important for artificial insemination. The aim of this study was to identify oestrous-specific bovine cervical mucus proteins that could be used to determine the optimal time for artificial insemination. Non-oestrous and controlled internal drug release (CIDR)-induced oestrous-stage mucus proteins were purified and subjected to surface-enhanced laser desorption/ionization time-of-flight mass spectrometry, sodium dodecyl sulphate polyacrylamide gel electrophoresis and MALDI-TOF/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…This study focused on the cervical mucus, whose production is induced during estrus in cattle. Previously, we have shown that bLF expression is significantly enhanced (more than two-fold) in bovine cervical mucus during estrus, as compared to non-estrus cattle [12].…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…This study focused on the cervical mucus, whose production is induced during estrus in cattle. Previously, we have shown that bLF expression is significantly enhanced (more than two-fold) in bovine cervical mucus during estrus, as compared to non-estrus cattle [12].…”
Section: Discussionmentioning
confidence: 83%
“…The supernatants were screened for the production of anti-bLF mAbs using ELISA. A 96-well ELISA micrometer plate (Nunc, Roskilde, Denmark) was coated with 50 µL of bLF extracted from bovine cervical mucus [12] (5 µg/mL in PBS) and incubated for 2 h at 37 • C. The coating solution was discarded, and the plates were washed twice with PBS and blocked with 1% BSA in 0.1% Tween 20 in PBS for 1 h at 37 °C. The anti-bLF (50 µL) was diluted in series of 1:10, 1:10 2 , 1:10 3 , 1:10 4 and 1:10 5 .…”
Section: Assesement Of Rat Anti-blf Mabsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the endometrial mucus layer covered on the surface of epithelial cells is constructing a biological barrier to affect the retention and absorption of the therapeutic agents, especially growth factors. 18,19 A healthy uterus of adult women secretes ∼3−4 g of endometrial mucus each 4 h. 20 The rapid turnover of mucus usually results in rapid discharge of the administrated therapeutic candidate in uterus cavity. Moreover, the endometrial mucus layer is a dynamic semipermeable barrier that can also capture some foreign substances including therapeutic agents, particulates, and pathogens followed by rapid clearance through the physiological secretion of mucus.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, not only the proliferation of endometrial glandular epithelial cells and luminal epithelial cells but also angiogenesis in injured uterus was observed after treatment with KGF. However, the endometrial mucus layer covered on the surface of epithelial cells is constructing a biological barrier to affect the retention and absorption of the therapeutic agents, especially growth factors. , A healthy uterus of adult women secretes ∼3–4 g of endometrial mucus each 4 h . The rapid turnover of mucus usually results in rapid discharge of the administrated therapeutic candidate in uterus cavity.…”
Section: Introductionmentioning
confidence: 99%